2008
DOI: 10.1210/jc.2007-1354
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Chromogranin A or Urine Fractionated Metanephrines Follow-Up Testing Improves the Diagnostic Accuracy of Plasma Fractionated Metanephrines for Pheochromocytoma

Abstract: Unless plasma fractionated metanephrines levels are elevated more than 4-fold above the upper limit of normal, patients with a positive plasma fractionated metanephrines test should be evaluated with urine fractionated metanephrines and serum/plasma CGA assays before being subjected to imaging or invasive diagnostic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 19 publications
1
49
0
4
Order By: Relevance
“…These methods have different practical advantages and disadvantages, but with the superior analytical specificity achieved with LC-MS/MS methods it can be expected that such methods should also offer improvements in diagnostic specificity. Indeed, a study from the Mayo Clinic, where LC-MS/MS has now replaced LCEC methods, indicated 1 034 positive results for plasma free metanephrines out of a total of 24 204 plasma samples analyzed, yielding a diagnostic specificity of more than 96 % [21]. This compares with previously reported diagnostic specificities for plasma free metanephrines measured by LCEC at the same center of 85 % [9], and at the NIH of 89 % [8].…”
Section: Future Challenges For Effective Diagnosismentioning
confidence: 78%
See 1 more Smart Citation
“…These methods have different practical advantages and disadvantages, but with the superior analytical specificity achieved with LC-MS/MS methods it can be expected that such methods should also offer improvements in diagnostic specificity. Indeed, a study from the Mayo Clinic, where LC-MS/MS has now replaced LCEC methods, indicated 1 034 positive results for plasma free metanephrines out of a total of 24 204 plasma samples analyzed, yielding a diagnostic specificity of more than 96 % [21]. This compares with previously reported diagnostic specificities for plasma free metanephrines measured by LCEC at the same center of 85 % [9], and at the NIH of 89 % [8].…”
Section: Future Challenges For Effective Diagnosismentioning
confidence: 78%
“…This method, however, cannot be used to distinguish false-from true-positive elevations in metanephrine. More recently, a study from the Mayo clinic advocated the use of urine fractionated metanephrines and chromogranin A as follow-up tests [21].…”
Section: Future Challenges For Effective Diagnosismentioning
confidence: 99%
“…19 The sympathetic PGLs secrete catecholamines. 19,20 Of the parasympathetic PGLs, most are nonsecretory. The PGLs and PCCs are very rare in children.…”
Section: Hereditary Paraganglioma/ Pheochromocytoma (Pgl/pcc) Syndromesmentioning
confidence: 99%
“…19 The catecholamines secreted by PGLs/PCCs may be epinephrine, norepinephrine, or dopamine. 20 The recommended case detection test is the plasma fractionated metanephrines achieving 82%-97% specificity with 96%-99% of sensitivity. 20 Negative test results exclude the existence of catecholamines.…”
Section: Hereditary Paraganglioma/ Pheochromocytoma (Pgl/pcc) Syndromesmentioning
confidence: 99%
See 1 more Smart Citation